Matrine Protects Intestinal Barrier Function via MicroRNA-155 Through ROCK1-Signaling Pathway - Yu, Dongdong; Ungureanu, Bogdan Silviu; Liu, Zhihua (Turkish Journal of Gastroenterology, 2023)
Background: The aim of this study was to investigate the protective effects on intestinal barrier function and tight junction by matrine via a small, non-coding RNA microRNA-155-signaling pathway. Materials and Methods: Tight junction protein and target gene expressions were determined through microRNA-155 inhibition or overexpression of Caco-2 cell line with or without the treatment of matrine. In order to further verify the role of matrine, dextran sulfate sodium-induced mice colitis was treated by matrine. MicroRNA-155 and ROCK1 expressions were detected in clinical specimens of acute obstruction patients. Results: Matrine could enhance the expression level of occludin, which might be inhibited by the overexpression of microRNA-155. After the transfection of the precursor of microRNA-155 into Caco-2 cells, ROCK1 expression was increased at both mRNA and protein levels. MicroRNA-155 inhibitor could decrease the ROCK1 expression after transfection. Furthermore, matrine could increase the permeability and decrease tight junction-associated proteins induced by dextran sulfate sodium-induced mice colitis. Clinical sample detection also found high levels of microRNA-155 in stercoral obstruction patients. Conclusions: Matrine could maintain the tight junction and protect the intestinal barrier from dysfunction. The molecular mechanism may be that matrine might inhibit microRNA-155 and increase the expression level of tight junction proteins. Cite this article as: Yu D, Su D, Liu Z. Matrine protects intestinal barrier function via MicroRNA-155 through ROCK1-signaling pathway. Turk J Gastroenterol. 2023;34(8):831-838.